Implementasi Metode Tsaqifa dalam Pembelajaran Membaca al-Qur’an Bagi Orang Dewasa - Supriyanto, Muhammad (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
This study aims to assess the substance of the material in the methodof learning the Quran tsaqifa. This method is specifically designed for adultswho have not been able to read the Quran or who never learned and stillverbatim read. In addition, the method also put a target on the learner inorder to quickly be able to read the Quran. Therefore, in this research, theauthor tries to re-examine whether the method is rapid, promising thecontent of what is taught is completely in accordance with the rules ofArabic writing is good and right. This study shows that the materialsubstance of this method known arabic (hijaiyah) approach Indonesiantranslation or Latin letters. However, the use of transliteration standardyet to implement them, like the letter “qo” written “ko” letter “sho” written“so”. In addition, there is also a writing error dot on the letter, such letter“ta” which should dot two above letter, written under the letter. It is perhapsworth noting because if wrong in awarding a point it will be wrong in thepronunciation. Nevertheless, the overall method is already making a positivecontribution to learning to read the Quran. Kedepanya expected to appearnew methods in reading the Koran rather comprehensive. Not merelyconcerned with the ability to read quickly, but also pay attention to thesubstance of the material well.